Nanoparticles‐Mediated CRISPR/Cas Gene Editing Delivery System. (25th March 2022) - Saw, Phei Er; Cui, Guo‐hui; Xu, Xiaoding
Abstract: CRISPR/Cas system has become one of the most powerful techologies in biomedical research, and has showed great potentials in the gene related diseases. However, efficient delivery systems of CRISPR/Cas to target cells remains challenging. In recent years, nanoparticles have showned great potentials for the delivery of CRISPR/Cas systems. This paper mainly approaches the development and new strategies of CRISPR/Cas delivery systems, as well as their application in the clinical diseases. By summarizing the CRISPR/Cas systems delivery, new strategies are expected for the gene therapy. Abstract : Editorial space : The CRISPR/Cas gene editing system relies on a delivery system to enter the cell so that it can perform its editing function. The CRISPR/Cas9 system can be packaged into viral or non‐viral vectors, which can be expressed in host cells and exert gene editing functions. The combination of nanoparticles and different vectors can promote the delivery of gene editing machinery.